Nested PCR-SSCP assay for the detection of p53 mutations in paraffin wax embedded bone tumours: improvement of sensitivity and fidelity. Issue 3 (June 1996) - Wang, L T; Smith, A; Iacopetta, B; Wood, D J; Papadimitriou, J M; Zheng, M H
Abstract : DNA extraction and PCR amplification from paraffin wax embedded bone tumour specimens present several difficulties, firstly, because of the abundant matrix they contain and, secondly, because decalcification often causes degradation of DNA. In this report, comparative studies were carried out to determine the most efficient method for DNA extraction and PCR amplification from such specimens. The results indicated that nested PCR produced appropriate strong reaction products with minimal background contamination. A method for DNA extraction from paraffin wax embedded bone tissue and a nested PCR-SSCP technique have been developed for use in such diagnostic specimens.